Establishing best practices for obesity and metabolic syndrome in liver transplantation: Insights from a modified Delphi-based controversies conference - Davis, Jessica P.E.; Henry, Zachary; Sharma, Pratima; Tsunoda, Shirley M.; Han, Hyosun; Orandi, Babak J.; Heimbach, Julie K.; Schulman, Allison R.; Tincopa, Monica A.; Argo, Curtis K.; Bittermann, Therese; Chacko, Kristina R.; et al. (American journal of transplantation, 2025)
Metabolic syndrome and obesity are prevalent and impact liver transplantation (LT) outcomes. Furthermore, the understanding of the complex physiology of obesity and availability of effective antiobesity interventions has developed rapidly. To bridge the current gap in practice guidance, the American Society for Transplantation Liver and Intestinal Community of Practice convened a controversies conference to develop expert recommendations for obesity management in the LT population. This conference used a modified Delphi method to generate consensus-based statements. Revisions at the virtual conference led to 26 best practice statements with high mean agreement and importance ratings (98% and 97%, respectively). The consensus emphasized the foundational role of nutrition and physical activity. Integration of emerging therapies such as incretin mimetics and identifying candidates for bariatric interventions are pivotal. Further research is essential to solidify these recommendations and adapt LT practices to the growing prevalence of obesity among patients and donors.